2008
DOI: 10.3155/1047-3289.58.3.369
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and Spatial Variations of Ammonia Emissions from an Open-Lot Dairy Operation

Abstract: There is a need for a robust and accurate technique to measure ammonia (NH3) emissions from animal feeding operations (AFOs) to obtain emission inventories and to develop abatement strategies. Two consecutive seasonal studies were conducted to measure NH3 emissions from an open-lot dairy in central Texas in July and December of 2005. Data including NH3 concentrations were collected and NH3 emission fluxes (EFls), emission rates (ERs), and emission factors (EFs) were calculated for the open-lot dairy. A protoco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
1

Year Published

2011
2011
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 5 publications
1
46
1
Order By: Relevance
“…Variations were likely due to temperature variations and uneven distribution of excretal returns at various GLASs at the dairy operation. Mukhtar et al [35] reported highly variable ammonia emission rates from open-lot surfaces at a free-stall dairy in Central Texas due to variable temperature, manure loading rates, and manure bacterial activity of the GLAS. ER is the emissions rate; GLAS is the ground level area sources; TNA is the total animal used to estimate ER at each GLAS; LQ is the lower quartile value; UQ is the upper quartile value; Medians followed by the same letter in columns for a particular compound are not significantly different (p > 0.05).…”
Section: Estimation Of Emission Rates (Ers) At the Dairy Operationmentioning
confidence: 99%
“…Variations were likely due to temperature variations and uneven distribution of excretal returns at various GLASs at the dairy operation. Mukhtar et al [35] reported highly variable ammonia emission rates from open-lot surfaces at a free-stall dairy in Central Texas due to variable temperature, manure loading rates, and manure bacterial activity of the GLAS. ER is the emissions rate; GLAS is the ground level area sources; TNA is the total animal used to estimate ER at each GLAS; LQ is the lower quartile value; UQ is the upper quartile value; Medians followed by the same letter in columns for a particular compound are not significantly different (p > 0.05).…”
Section: Estimation Of Emission Rates (Ers) At the Dairy Operationmentioning
confidence: 99%
“…The differences were likely because of temperature variations and uneven distribution of excreta at different GLAS in the dairy operation. Mukhtar et al 27 reported highly variable NH 3 emission factors from open-lot surfaces in a free-stall dairy in central Texas because of variable temperature, manure loading rates, and manure bacterial activity of the GLAS.…”
Section: Estimation Of Ers In Different Glasmentioning
confidence: 99%
“…Others have also reported high variations because of the disparate distribution of manure in the CH 4 and N 2 O emissions from the barn and animal manure storage facilities. 14,27 CH 4 Concentrations. During the summer, the highest average CH 4 concentration was measured from the settling basin, followed by the primary lagoon and loafing pen ( Table 3).…”
Section: Ghg Concentrations In Different Glasmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research reported that ambient temperature, soil moisture, and manure composition are the primary factors controlling anaerobic decomposition in feedyard soils (Miller and Varel, 2001). Mukhtar et al (2008) also reported highly variable ammonia (NH 3 ) emissions from open-lot sources in a free-stall dairy in central Texas due to variable manure loading rates.…”
Section: Phenol and P-cresol Concentrations In Different Glasmentioning
confidence: 99%